Gambaran Sikap Petugas Administrasi terhadap Pasien Rawat Jalan di Rumah Sakit Umum Bhakti Asih Tahun 2025 - Widya Cahya Anggraini; Ria Efkelin; Ratu Chairunnisa (Universitas Muhammadiyah Manado, 2025)
Administrative officers are the frontline of hospital service systems, playing not only an administrative role but also shaping first impressions, influencing trust, and serving as key determinants of initial patient satisfaction within the dynamic and time-sensitive context of outpatient care. This study aims to describe the attitudes of administrative staff toward outpatients at Bhakti Asih General Hospital in 2025. The research employed a descriptive quantitative method using accidental sampling. A total of 50 patients from the internal medicine and cardiology clinics served as respondents. The results showed that the affective dimension was rated as good by 33 respondents (66.0%), the cognitive dimension by 33 respondents (66,0%), and the behavioral dimension by 33 respondents (66,0%). Although most responses were in the “good” category, some respondents gave “fairly good” ratings, particularly regarding emotional communication, information delivery, and responsiveness. In conclusion, the attitudes of administrative staff are generally good, although improvements are still needed to ensure equitable service quality.